2013
DOI: 10.3732/ajb.1300055
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and domestication of carrot (Daucus carota subsp. sativus) (Apiaceae)

Abstract: Comparing the genetic diversity of wild and cultivated accessions suggested the absence of a genetic bottleneck during carrot domestication. In conjunction with historical documents, our results suggest an origin of domesticated carrot in Central Asia. Wild carrots from North America were likely introduced as weeds with European colonization. These results provide answers to long-debated questions of carrot evolution and domestication and inform germplasm curators and breeders on genetic substructure of carrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
171
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(204 citation statements)
references
References 74 publications
26
171
3
4
Order By: Relevance
“…In contrast, western cultivars clearly separated from wild and eastern cultivated carrots, and some inbred lines (I3 and I4) have a purified genetic pattern shared with western cultivated accessions, reflecting the intensive breeding practiced in western regions. Nucleotide diversity (π) 25 estimates showed that wild carrots have a slightly higher level of genetic diversity than cultivated carrots (Supplementary Table 18), indicating the occurrence of a limited domestication bottleneck, consistent with previous findings 3,26 . When D. carota subspecies, which have morphological characteristics contributing to their sexual isolation relative to carrot 27 , were excluded from diversity estimates, this observation was more evident from comparative analysis (wild, π = 9.5 × 10 −4 versus cultivated, π = 8.6 × 10 −4 ).…”
Section: A R T I C L E Ssupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, western cultivars clearly separated from wild and eastern cultivated carrots, and some inbred lines (I3 and I4) have a purified genetic pattern shared with western cultivated accessions, reflecting the intensive breeding practiced in western regions. Nucleotide diversity (π) 25 estimates showed that wild carrots have a slightly higher level of genetic diversity than cultivated carrots (Supplementary Table 18), indicating the occurrence of a limited domestication bottleneck, consistent with previous findings 3,26 . When D. carota subspecies, which have morphological characteristics contributing to their sexual isolation relative to carrot 27 , were excluded from diversity estimates, this observation was more evident from comparative analysis (wild, π = 9.5 × 10 −4 versus cultivated, π = 8.6 × 10 −4 ).…”
Section: A R T I C L E Ssupporting
confidence: 88%
“…We identified 3,267 (10% of the total) regulatory genes in carrot, a number similar to that in tomato (3,209 regulatory genes) and rice (3,203 npg regulatory gene expansion, with ~33% of these genes retained after the two carrot WGDs, demonstrating the evolutionary impact of large-scale duplications on plant regulatory network diversity 34 (Supplementary Table 27). Six regulatory gene families involved in lineage-specific duplications were expanded in carrot (Supplementary Table 28).…”
Section: Regulatory Genesmentioning
confidence: 85%
See 1 more Smart Citation
“…However, this is not always the case, since in some crops, e.g., in carrot (Daucus carota subsp. sativus), no decrease of genetic diversity occurred during domestication (Iorizzo et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, new mutations may be important and the impact of epigenetic changes remains substantially unexplored. In many self-incompatible crops, such as many fruit trees [108], carrot (Daucus carota) [109], or scarlet runner bean (Phaseolus coccineus [110]), genetic diversity will remain high in cultivated forms and may be equivalent to wild relatives. Furthermore, the practice of grafting may preserve within-individual heterozygosity, while leading to very low stand or population level variation (e.g., [103]).…”
Section: Reduced Genetic Diversity Of Cropsmentioning
confidence: 99%